2010
DOI: 10.1016/j.yhbeh.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Women's interest in visual sexual stimuli varies with menstrual cycle phase at first exposure and predicts later interest

Abstract: This study investigated whether women’s interest in visual sexual stimuli varied with their hormonal state. Viewing times of 30 women, 15 normal cycling (NC) and 15 oral contracepting (OC), to sexually explicit photos were measured at three different times. NC Women were tested during their menstrual, periovulatory, and luteal phases, and OC Women were tested at equivalent temporal intervals. Subjects viewed stimuli as long as desired, thus viewing time measured subject interest. Subjective ratings of stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…Women in the follicular phase also reported heightened levels of sexual arousal to erotic films. Similarly, Wallen and Rupp (2010) reported that women first tested in the follicular phase showed increased visual sexual interest in sexual stimuli in subsequent sessions compared to women first tested in their luteal phase.…”
Section: Intra-sex Differences and The Menstrual Cyclementioning
confidence: 88%
See 1 more Smart Citation
“…Women in the follicular phase also reported heightened levels of sexual arousal to erotic films. Similarly, Wallen and Rupp (2010) reported that women first tested in the follicular phase showed increased visual sexual interest in sexual stimuli in subsequent sessions compared to women first tested in their luteal phase.…”
Section: Intra-sex Differences and The Menstrual Cyclementioning
confidence: 88%
“…Little research has been conducted to explore whether hormones affect sexual fantasies and the category-specificity of visual sexual interests of women across the cycle (Bullivant et al, 2004;Slob et al, 1996;Wallen & Rupp, 2010). Few studies have been conducted to investigate changes in both the frequency and content of women's sexual fantasies continuously across an entire menstrual cycle using an accurate measure of ovulation.…”
Section: Intra-sex Differences and The Menstrual Cyclementioning
confidence: 99%
“…Dawson, Suschinsky, & Lalumière, 2012). Some studies also indicate that menstrual phase during the initial exposure to sexual stimuli may have a stronger effect on women's sexual responses than the actual cycle phase at the time of testing but other studies do not (e.g., Suschinsky et al, 2014;Wallen & Rupp, 2010cf. Bossio et al, 2014 Another limitation in interpretation concerns our findings on WHR.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that fertility status at first exposure to sexual stimuli has a significant effect on subsequent sexual responses to such stimuli Wallen & Rupp, 2010). Thus cycle phase during the initial exposure to sexual stimuli may have a stronger effect on women's sexual responses than the actual cycle phase at the time of testing.…”
Section: The Role Of Waist-to-hip Ratio and Menstrual Cycle Phasementioning
confidence: 99%
“…Oral contraceptive users reveal a progressive increasing interest if first tested during menstruation (9). The number of fixations on the body has the same significant increase in males and females in case of erotic versus non erotic body images (10).…”
Section: Primary Physiologic Effectsmentioning
confidence: 99%